Inoculação de bactérias promotoras de crescimento na cultura da alface - Machado , Fabiana Ribeiro (2021)
Plant growth promoting bacteria (BPCV) are an alternative for increasing the productivity of several crops, including lettuce. Several reports are found in the literature with the use of plant growth-promoting bacteria in the lettuce crop, but the most seek increments during the production of seedlings. Aiming to provide increments in the field cultivation of lettuce and to generate subsidies to technicians and producers, the aim of this work was to study the influence of the application of commercial products based on Azospirillum brasilense, Bacillus subtilis + B. megaterium and Pseudomonas fluorescens, on agronomic characteristics and quality of crisp lettuce. The experiment was implemented in two locations, in a randomized block design, in a 4 x 3 factorial scheme, with four replications. The first factor refers to the application of different BPCV: control; inoculations with A. brasilense; B. subtilis + B. megaterium and P. fluorescens. The second factor was composed of three periods of application of the BPCV, the first period on the day of seedling transplantation (DT) and the second at 15 DAT and the third on the DT + 15 DAT. At 15 DAT, the relative chlorophyll content, plant height, head diameter, number of leaves per plant, leaf area, leaf dry mass, stem dry mass, root dry mass, total dry mass, root volume were evaluated and root length. At harvest, the same variables were analyzed, in addition to leaf fresh mass, stem fresh mass, head fresh mass, root fresh mass, total fresh mass and leaf nitrogen, phosphorus and potassium contents. Despite the increase in stem and root dry mass at 15 DAT, at harvest time, no significant results were observed at harvest. Although A. brasilense increased the MST when applied to DT + 15 DAT and when compared to P. fluorescens was superior, when compared to the control with the other treatments, no significant results were obtained for the agronomic characteristics and quality of the culture of the lettuce crisp cultivar Vera. Among the likely explanations, it can be highlighted that the nutrient contents in the soil and the planting and coverage fertilization were sufficient to meet the nutritional requirements of the crop, minimizing the possible positive effects expected due to the inoculation with BPCV, in addition to the possibility of this cultivar do not show positive interaction with these microorganisms.